Functional expansion of human tRNA synthetases achieved by structural inventions - Guo, Min (2010)
Known as an essential component of the translational apparatus, the aminoacyl-tRNA synthetase family catalyzes the first step reaction in protein synthesis, that is, to specifically attach each amino acid to its cognate tRNA. While preserving this essential role, tRNA synthetases developed other roles during evolution. Human tRNA synthetases, in particular, have diverse functions in different pathways involving angiogenesis, inflammation and apoptosis. The functional diversity is further illustrated in the association with various diseases through genetic mutations that do not affect aminoacylation or protein synthesis. Here we review the accumulated knowledge on how human tRNA synthetases used structural inventions to achieve functional expansions.